Pemanfaatan Sumber Belajar Berbasis Multimedia DalamMeningkatkan Efektivitas Pembelajaran PendidikanAgama Islam Kelas X DI SMA Muhammadiyah 1 SurakataTahun Pelajaran 2014-2015 - Yasir Fahmi, Muhammad, Drs. Saifuddin Zuhri, M.Ag (2016)
The development of knowledge and technology support much the efforts of renewal in the use of technology outcomes in the learning process. The teachers are demanded to be able to use the equipments provided by the school, and it is possible that the equipment is suitable with the advance of era. In a teaching-learning process, two very important elements are the teaching method and the learning multimedia. These two aspects are interrelated. The selection on one of learning method of course will influence the kind of suitable learning multimedia, therefore, things that must be considered in selecting multimedia, among other, are the objectives of learning, the kind of task and the response hoped that will be mastered by the students after the learning lasts, and the learning context including the students' characteristics. Meanwhile, the problem statement of this research is: how is the use of the multimedia-based learning source in increasing the effectiveness of learning of Islamic religious education of Grade X in SMA Muhamaadiyah 1 Surakarta? The purpose is to describe the use of the multimedia-based learning source in increasing the effectiveness of learning of Islamic religious education of Grade X in SMA Muhamaadiyah 1 Surakarta. Meanwhile, the benefits of this research are that it can give theoretical as well as practical benefits. Also, the benefits of the study is that it can give motivation, suggestion, and guidance to develop a creative and interesting learning through the use of multimedia for the teachers. This research is categorized in a field research. Subjects of this research ae teachers who teach the subject of Islamic Religious Education and the students of Grade X of SMA Muhammadiyah 1 Surakarta, whereas, the object of the research is the learning multimedia. The data collection used the methods of observation, interview, and documentation, meanwhile, the method of data analysis is inductive. The conclusion is that the use of multimedia is very important in increasing the effectiveness of students. It can be viewed that before using the multimedia, the scores obtained by the students in the daily test were varied with the amounts of average score of daily test were: the lowest score is the score 50- 65 as much as 65%, the score 70-80 as much as 25%, the score 90-95 as much as 10%, meanwhile after using the learning process that used multimedia, the outcomes of the students' average score of daily test obtained the lowest score 70- 75 as much as 65%, the score 80-85 as much as 15%, and the score 90-95 as much as 20%. Hence, the learning without using multimedia has the lowest score 50, meanwhile, the learning using multimedia has the lowest score as much as 70, so, all students exceeded the score limit by using the mulimedia, because by using the multimedia, time used for teaching is not vainly spent. It is the thing that makes the time of learning becomes effective and the learning atmosphere becomes efficient by using the multimedia, therefore, the learning becomes more interesting, concrete, and interactive.